Interest in Hypothetical Preexposure Prophylaxis Against Herpes Simplex Virus: A Cross-Sectional Survey. Issue 8 (August 2021) - Tan, Darrell H. S.; Tavangar, Farideh; Fusca, Laura; Ross, Patrick; Hull, Mark W.; Grennan, Troy; Bayoumi, Ahmed M.; Burchell, Ann N.
Abstract : Abstract: We surveyed 383 men who have sex with men attending sexual health clinics regarding interest in hypothetical preexposure prophylaxis against herpes simplex virus. Overall interest was 62.5% and was associated with the number of different sexually transmitted infections previously diagnosed (adjusted odds ratio, 1.9; 95% confidence interval, 1.5–2.6) and previous HIV preexposure prophylaxis use (adjusted odds ratio, 2.9; 95% confidence interval, 1.1–8.3). Abstract : This cross-sectional survey in Toronto and Vancouver, Canada, found moderately high willingness to use a hypothetical preexposure prophylaxis against herpes simplex virus among men who have sex with men.Supplemental digital content is available in the text.